Pengaruh Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan PT Guna Cipta Sinergi Jakarta Barat - Pancaningrum, Yessi Meilani; Aprillia, Frida; Siboro, Sonny Fransisco (CV Warnak Johanna Nusantara, 2026)
This study aims to analyze the effect of work discipline and work motivation on the performance of employees at PT Guna Cipta Sinergi in West Jakarta. The research population consists of all 163 employees of PT Guna Cipta Sinergi, with a sample of 62 respondents determined using the Slovin formula with a margin of error of 10%. This study uses a quantitative approach with multiple linear regression analysis. Data were collected through a questionnaire with a Likert scale that had been tested for validity and reliability. The analysis tool used was SPSS version 25. The results showed that: (1) Work discipline had a positive and significant effect on employee performance with a t-value of 2.037 > t-table 2.001 and significance of 0.046 < 0.05; (2) Work motivation does not have a significant effect on employee performance with a t-value of 1.209 < t-table 2.001 and significance of 0.231 > 0.05; (3) Simultaneously, work discipline and work motivation have a significant effect on employee performance with a calculated F value of 14.313 > F table 3.15 and significance of 0.000 < 0.05. The coefficient of determination (Adjusted R²) value of 30.4% indicates that both variables can explain 30.4% of the variation in employee performance, while the remaining 69.6% is explained by other factors. These findings imply that companies need to maintain work discipline policies and evaluate motivation strategies to optimize employee performance.